Numerical and experimental study of dynamic buckling behavior of a J-stiffened composite panel under in-plane shear. (15th April 2017) - Bai, Ruixiang; Lei, Zhenkun; Wei, Xiao; Tao, Wang; Yan, Cheng
Abstract: The buckling behavior and failure mode of a composite panel stiffened by J-shaped stringers under in-plane shear is studied by experiments and numerical analysis. Digital fringe projection profilometry was applied to monitor and measure the buckling morphology changes of the stiffened composite panel during in-plane shearing, which was verified by strain gauge measurement. Numerical simulation was performed using the finite element method to predict the failure load and buckling modes of the stiffened composite panel under in-plane shear. Numerical results showed good agreement with the full-field optical buckling measurement. The combination of experimental and numerical prediction can be effective in revealing the deformation process and failure mechanism of the stiffened composite panel.